Being a Psychotherapist in Times of the Novel Coronavirus Disease: Stress-Level, Job Anxiety, and Fear of Coronavirus Disease Infection in More Than 1,500 Psychotherapists in Austria - Probst, Thomas; Humer, Elke; Stippl, Peter; Pieh, Christoph (Frontiers in Psychology, 2020)
This study investigated stress-level, degree of job-related anxiety, and fear of COVID-19 infection in psychotherapists in the first weeks of the COVID-19 lockdown in Austria. 1,547 psychotherapists participated in an online survey, assessing stress (Perceived Stress Scale-10), work-related worries and fears of existence (Job Anxiety Scale), fear of COVID-19 infection during psychotherapy in personal contact and adherence to five protective measures against COVID-19 infection during psychotherapy in personal contact. Stress-levels were higher than in a representative sample (p < .001). When psychotherapy was the sole income, stress-level (p = .020) and job anxiety (p < .001) were higher. Experiences with remote psychotherapy, the psychotherapy format used during COVID-19, as well as reductions in number of patients treated during COVID-19 had no effect on stress-level or job anxiety. Psychotherapists still conducting psychotherapy in personal contact during COVID-19 reported less fear of infection compared to those conducting no psychotherapy in personal contact (p < .001), whereby the fear of infection was further reduced when they were more able to adhere to protective measures against COVID-19 (p < .01). Mental hygiene is important for psychotherapists to manage stress and job-related anxiety during COVID-19, especially in those whose income relies on psychotherapy.